Implementation viability of ASETs at Nai Teri indigenous sector, for renewable electric energy generation - Amador, María Jesús (2025)
This research aims to give visibility to the reality faced by people living in sectors not covered by the national electrical grid, particularly in remote regions and within indigenous reserves. The Nai Teri region is contemplated as a case study. It shows the impact that the absence of electrical resources represents on the quality of life of these people and how their customs and daily lives develop without electricity. On the other hand, it is mentioned how these people would benefit from the application of energy generation technologies based on resources available in the area. Research is carried out on types of ASETs (Appropriate Sustainable Energy Technologies) that could be implemented and their viability according to transportation, installation, and maintenance. It’s concluded that the most feasible way to produce energy in the area is through solar panels, for which investment by third parties is necessary, whether government, electric companies, or private capital.